Peningkatan Niat Pembelian Ulang dengan Kualitas Layanan dan Word of Mouth di Ha-Ka Restoran : Peran Kepuasan Pelanggan sebagai mediasi - Tjitjih Dewiasih; Bonifasius Nainggolan (LPPM and Travel Operation Department Universitas Asa Indonesia, 2022)
The study examines the role of service quality and WOM on repurchase intention through customer satisfaction at restaurants serving Indonesian and Western food in Central Jakarta. Hypothesis testing using SEM with the help of PLS-SEM 2.3.9. Customers of restaurants were given a questionnaire as part of the study's survey methodology. The sample determination criteria use the purposive sampling method: a customer who has made at least two purchases at the restaurant. The number of customers who became the final sample was 250 respondents. The statements presented on the questionnaire have referred to previous studies. The results showed that service quality and WOM significantly and favorably impact customer satisfaction and intent to repurchase. Repurchase intention is greatly and directly influenced by customer satisfaction. Customer satisfaction significantly affects the indirect effect of service quality and WOM on repurchase intention. This study demonstrates that WOM's direct impact on repurchase intention is most significant. Compared to WOM's influence, service quality's effect on repurchase intention is more strongly mediated by customer satisfaction.